Bortezomib consolidation following autologous transplant in younger and older patients with newly diagnosed multiple myeloma in two phase III trials. (19th July 2019) - Straka, Christian; Knop, Stefan; Vogel, Martin; Müller, Jürgen; Kropff, Martin; Metzner, Bernd; Langer, Christian; Sayer, Herbert; Jung, Wolfram; Dürk, Heinz A.; Salwender, Hans; Wandt, Hannes; et al.
Abstract: Objective: A post hoc analysis of two phase III trials was carried out to explore the influence of age and treatment factors on the effect of bortezomib consolidation on progression‐free survival (PFS) post autologous stem cell transplantation (ASCT). Methods: Patients with newly diagnosed multiple myeloma were assigned to one of two trials (ClinicalTrials.gov IDs: NCT00416273, NCT00416208), which were conducted in parallel, based on age (18‐60 or 61‐75 years, respectively). Following induction and ASCT, patients were randomized 1:1 to four 35‐day cycles of bortezomib consolidation (1.6 mg/m 2 IV on days 1, 8, 15, 22) or observation only. Results: Median PFS with bortezomib consolidation vs observation was 33.6 vs 29.0 months ( P  = 0.3599) in patients aged 18‐60 years (n = 202), and 33.4 vs 26.4 months ( P  = 0.0073) in patients aged 61‐75 years (n = 155), respectively. Bortezomib consolidation post‐ASCT appeared to equalize outcomes between older and younger patients who received prior treatment of differing intensity. This suggests that the effect of consolidation may be relative and may depend on the composition and intensity of induction and high‐dose therapy. Conclusion: Older patients receiving less intensive prior treatment could experience a larger PFS benefit from bortezomib consolidation.